Cancer‐related somatic mutations alter adenosine A1 receptor pharmacology—A focus on mutations in the loops and C‐terminus. Issue 6 (23rd May 2022) - Wang, Xuesong; Jespers, Willem; de Waal, Just J.; Wolff, Kim A. N.; van Uden, Liedeke; IJzerman, Adriaan P.; van Westen, Gerard J. P.; Heitman, Laura H.
Abstract: G protein‐coupled receptors (GPCRs) are known to be involved in tumor progression and metastasis. The adenosine A1 receptor (A1 AR) has been detected to be over‐expressed in various cancer cell lines. However, the role of A1 AR in tumor development is not yet well characterized. A series of A1 AR mutations were identified in the Cancer Genome Atlas from cancer patient samples. In this study, we have investigated the pharmacology of mutations located outside of the 7‐transmembrane domain by using a "single‐GPCR‐one‐G protein" yeast system. Concentration‐growth curves were obtained with the full agonist CPA for 12 mutant receptors and compared to the wild‐type hA1 AR. Most mutations located at the extracellular loops (EL) reduced the levels of constitutive activity of the receptor and agonist potency. For mutants at the intracellular loops (ILs) of the receptor, an increased constitutive activity was found for mutant receptor L211R 5.69, while a decreased constitutive activity and agonist response were found for mutant receptor L113F 34.51 . Lastly, mutations identified on the C‐terminus did not significantly influence the pharmacological function of the receptor. A selection of mutations was also investigated in a mammalian system. Overall, similar effects on receptor activation compared to the yeast system were found with mutations located at the EL, but some contradictory effects were observed for mutations located at the IL. Taken together, this study will enrich the insight of A1 AR structure and function, enlightening the consequences of these mutations in cancer. Ultimately, this may provide potential precision medicine in cancer treatment.